Socialization Process in the Brazilian Public Sector: The Case of Petrobras (British Journal of Multidisciplinary and Advanced Studies, 2024)
This research explores socialization in the Brazilian public sector (BPS) and Petrobras, the largest semi-public company in the country. It investigates the challenges faced by new employees and the factors influencing socialization in the public sector. Using Behavioral Event Interviews with experts, the study aims to understand how dissatisfied employees handle their relationship with work and the company when they perceive no risk of being fired. It also explores the situation when new employees reach their limit of coping but choose not quitting the job due to the high investment and benefits. The study also examines how the socioeconomic context influences socialization in the public sector, as new employees expect to spend their entire productive years in the company until retirement.